Natural rosin-grafted nanoparticles for extremely-robust and eco-friendly antifouling coating with controllable liquid transport. (1st May 2022) - Qing, Yongquan; Long, Cai; An, Kai; Liu, Changsheng
Abstract: Owing to their highly efficient antifouling function, superhydrophobic coatings show great potential applications in both daily-life and industrial areas. Real-world applications, however, still encounter challenges, with the central concern being the mechanical robustness and eco-friendliness. Here, we developed a robust and eco-friendly superhydrophobic coating (RESC) by hybrid synergistic assembly between naturally-sourced raw material (rosin) and hydrophobic nanoparticles. The resulting product can reserve superhydrophobicity after tape-peeling, sandpaper abrasion, and even high-speed water jets up to 20 m/s. Additionally, the coating can prevent adhesion by water-based contaminants, and could repel solid contaminants upon washing with water. Intriguingly, when infused with silicone oil, the coating could easily repel low-surface-energy droplets covered with hot water, oil, and fouled oil, and these droplets could be transported controllably along a desired wetted path on the slippery surface. These results suggest that coatings with integrated functionalities can be potentially used under various harsh environments such as those encountered in chemical engineering, infrastructure, and biomedical applications. Graphical abstract: Image 1